Prostate Cancer: What About Reproducibility of Decision Made at Multidisciplinary Team Management? - Bayoud, Younes; Loock, Pierre Yves; Messaoudi, Rabah; Ripert, Thomas; Pierrevelcin, Jean; Kozal, Sebastien; Leon, Priscilla; Kamdoum, Majorlaine; Irène, Cholley; Menard, Johann (Urology Journal, 2015)
Purpose: The prostate cancer (PCa) treatment is multimodal. Thus multidisciplinary team management (MDTM) decision-making process appears as a tool to answer all aspects of PCa treatment. Our aim was to evaluate the reproducibility of therapeutic decisions made at MDTM. Materials and Methods: We compared therapeutic decisions of PCa by presenting the same file of patient under a fake identity after 6 to 12 months from the first presentation. Forty-nine files of radical prostatectomy (RP) (28 pT2, 21 pT3) performed for clinical localized PCa were represented at MDTM which included urologist, oncologist, pathologist and radiologist. Analysis of therapeutic decisions comprised criteria such as: TNM stage, Gleason score, margin status and comorbidities. The reproducibility was assessed statistically by Kappa coefficient. Results: Study subjects included 49 patients who underwent radical prostatectomy (RP). The mean age was similar in pT2 and pT3 groups (P = .09). The mean serum PSA value was 8.32 ng/mL (range, 3.56-19.5) in pT2 group and 9.4 ng/mL (range, 3.8-22) in pT3 group. The margin status in pT2 and pT3 groups was positive in 25.0% and 47.6%, respectively. The decisions made at first and second MDTM for pT2 group were the same in 100% of cases with a perfect kappa coefficient (k = 1). In the group of pT3 (n = 21), the decisions were different in 33% at the second MDTM in comparison to the first MDTM. Especially for pT3b only 29% were reproducible decision with a slight agreement (k = 0.1). Concerning pT3a, 86% of the decisions were reproducible with a substantial agreement (k = 0.74). Conclusion: We showed a reliability and reproducibility of decision made at MDTM when guidelines are well defined. The therapeutic attitudes were less reproducible in locally advanced PCa but decision concerning those cases should be made in the setting of guidelines.